Dogs of nomadic pastoralists in northern Kenya are reservoirs of plasmid-mediated cephalosporin- and quinolone-resistant Escherichia coli, including pandemic clone B2-O25-ST131 - Albrechtova, Katerina; Dolejska, Monika; Cizek, Alois; Tausova, Dagmar; Klimes, Jiri; Bebora, Lily; Literak, Ivan (Antimicrobial agents and chemotherapy, 2012)
Resistance in Escherichia coli isolates colonizing gastrointestinal tracts of dogs, cats, and their owners in Northern Kenya was investigated with an emphasis on extended-spectrum beta-lactamases (ESBLs). Totals of 47 (22%, n = 216), 2 (4%, n = 50), and 4 (17%, n = 23) CTX-M-15-producing E. coli isolates were obtained from dogs, cats, and humans, respectively. CTX-M-15-producing E. coli isolates with identical PFGE profiles were detected in animals and humans living in the same area.
Keywords: Animals; chinolony; Quinolones; Escherichia coli; beta-laktamasy; lidé; kočky; Dogs; cefalosporiny; beta-Lactamases; Cats; plazmidy; Cephalosporins; mnohočetná bakteriální léková rezistence; Keňa; Drug Resistance, Multiple, Bacterial; Plasmids; zvířata; Kenya; psi; Humans